AGENDA SETTING DALAM KEBIJAKAN PERATURAN DAERAH NOMOR 2 TAHUN 2016 TENTANG PARIWISATA HALAL PROVINSI NUSA TENGGARA BARAT - Anggraeni, Vivin; Bandiyah, Bandiyah; Noak, Piers Andreas (Jurnal Nawala Politika; 2019, 2019)
ABSTRACT   This study aims to provide an overview of the setting agenda in the regional regulation policy number 2 of 2016 concerning halal tourism in NTB. Province NTB is the first area in Indonesia that succeeded in formulating a regional regulation of halal tourism. The theory used in this study Setting Agenda Theory from John Kingdon. Acording to John Kingdon , The Setting Agenda Theory is divided into three stream, consisting of the flow of problem, the flow of policy and the political flow. This study uses descriptive qualitative. The results of the research found are first,the lack of public understanding of halal tourism and the conflict between community groups. Second, the lack of socialization from the Department of Tourism to the public about halal tourism. Third, there are pros and cons in the process of formulating the regional regulationof halal tourism.                                                                                                Keywords: Setting Agenda, Regional Regulation, Halal Tourism